A novel fluorescent covalent organic framework containing boric acid groups for selective capture and sensing of cis-diol molecules. Issue 46 (24th November 2020) - Chang, Zhaosen; Liang, Ying; Wang, Shunli; Qiu, Lu; Lu, Yan; Feng, Lijuan; Sui, Zhuyin; Chen, Qi
Abstract : A novel fluorescent covalent organic framework containing boric acid groups was prepared for selective uptake and optical sensing of cis -diol. Abstract : Owing to specific formation of five-membered or six-membered cyclic esters between boric acid groups and cis -diol molecules, boric acid bearing fluorescent materials can not only selectively capture but also specifically identify cis -diol substances. In this work, a novel covalent organic framework containing boric acid groups (COF-BA ) was prepared through post-modification via the aza-Diels–Alder cycloaddition reaction. COF-BA with good stability, a permanent pore structure, a high specific surface area (606 m 2 g −1 ) and a uniform pore size (2.59 nm) exhibited unique selectivity toward the cis -diol guest molecule 1, 2-dihydroxyanthracene-9, 10-dione (1, 2-Doa) with a high adsorption capacity of 177.95 mg g −1 . However, as for the isomers of 1, 2-Doa (1, 4-dihydroxyanthracene-9, 10-dione and 2, 6-dihydroxyanthracene-9, 10-dione), the corresponding uptake capacities are distinctively decreased to 40.86 mg g −1 and 3.05 mg g −1, respectively. It is worth noting that the COF-BA can be recovered and recycled. Moreover, because the formation of the quinoline enhanced the conjugation effect of the COF skeleton, it was unexpectedly found that COF-BA possessed an intrinsic fluorescence property and could be used as an optical sensor for 1, 2-Doa.